The impact of Scout and Guide attendance on cognitive ability trajectories in childhood and the late life impact of this effect on risk of adult mental and physical ill health - A 1950s cohort study linked to administrative data. - Dibben, Chris; Patel, Kishan; Wiliamson, Lee (International Journal of Population Data Science, 2025)
Objectives Informal educational programmes focused on youth development appear to improve health and well-being at time of involvement. Less is known about their effect on cognitive ability and educational outcomes. We investigate their impact on cognitive ability trajectories in childhood and then general health and mental health in mid-life using the Aberdeen Children of the 1950s (ACONF) cohort linked to prescribing data. Methods We use a subset (n = 1333) of the ACONF cohort, born 1950–56, in Aberdeen Scotland, who took part in Family and Reading Surveys in 1964 and a follow-up questionnaire in 2001 linked to administrative data prescribing records. We explore exposure to youth development focused clubs in childhood, on trajectories in cognitive ability from age 7 to age 9 and the extent that this change predicts education outcomes, later life socio-economic position and then self-reported general health around age 50 and mental ill health as measured by prescription data. Results Being a member of the Scouts/Guides (G&S) was associated with a significantly higher age 9 cognitive ability score, controlling for age 7 cognitive ability in unadjusted and adjusted models. This difference was stronger for children from more economically disadvantaged backgrounds. This ‘acceleration’ in cognitive ability development was associated with better educational outcomes and adult socio-economic position and this in turn predicted better later life health but not mental health. Conclusion Membership of informal educational organisations such as the scouts and guides appears to have a direct impact on cognitive development in children, especially those from more economically disadvantaged backgrounds with lifelong impacts Because these organisations are provided by volunteers and charitable organisations, they represent a relatively low cost intervention, with substantial impacts, it would seem sensible to encourage their availability.